THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING THE MOTHER LANGUAGE IN PRIMARY GRADES TODAY (American Journal of Interdisciplinary Research and Development, 2025)
Nowadays, the process of digital transformation in the education system is rapidly advancing. In particular, the use of information and communication technologies (ICT) in primary education plays a crucial role in developing students’ knowledge, skills, and competencies. Integrating ICT tools into the teaching of the mother tongue can make lessons more effective, interactive, and engaging. This, in turn, enhances students’ comprehension and encourages independent thinking.